Hot melt emulsification shear method for solid lipid-based suspension: from laboratory-scale to pilot-scale production - Chao Li; Wenqing Xie; Liwen Yuan; Mubbashar Abbas; Dongmei Chen; Shuyu Xie (BMC, 2023)
Abstract The clinical application of solid lipid particles (SLPs) is hampered due to the need for advanced nano/micro-suspension production technology. This research aims to establish a pilot-scale production line employing high-speed shears as emulsification equipment. The primary purpose is to manufacture nano/micro-suspensions using solid lipid particles (SLPs). The study also exhaustively introduces and analyzes the regulatory schemes for process parameters and formulations at various stages of production. The process and formulation endured optimization through orthogonal or single-factor tests at various production steps: laboratory research, small-scale trial production, and pilot production. Quality standards for the product were determined, and key parameters were obtained at each stage. The laboratory research demonstrated that the optimal SLPs comprised 15 mL 3% polyvinyl alcohol (PVA) per 1.0 g tilmicosin and 2.5 g carnauba wax (WAX). During small-scale production, modifications were made to the volume of the aqueous phase, emulsifier concentration, and emulsification strength, setting them to 16 mL, 5%, and 2200 r/min, respectively. In the pilot production stage, the shear time was considered optimal at eight min. The impurity, content, polydispersion coefficient (PDI), and size of the pilot product were < 3%, 5%, 0.385 and 2.64 μm, respectively. Among the several parameters studied, heating temperature, drug-lipid ratio, and emulsifier concentration were identified as the main factors affecting product quality, and they were regulated at 100℃, 1:3, and 5%, respectively. A novel hot melt emulsification shear method aided the development of a new solid lipid-based suspension from its preliminary stages in the laboratory to pilot production. This innovation is expected to enhance solid lipid-based suspensions' industrial evolution extensively.